Institutional capacity of labor supervision and control bodies: international standards and problems of implementation into Ukrainian legislation - Ostrovskyi, Serhii; Sivkov, Serhiy; Zadereiko, Svitlana; Voloshanivska, Tetiana; LEHEZA, Yevhen (Jurnal Cita Hukum, 2026)
The article examines the institutional capacity of labor supervision and control bodies in the context of international standards and the features of their implementation in the legislation of Ukraine. The main approaches of the International Labor Organization and the European Union to the organization of the labor inspection system are analyzed, in particular, regarding ensuring the independence of control bodies, the adequacy of their powers, and human and financial support. The current state of legal regulation of the activities of labor supervision bodies in Ukraine is outlined and key problems related to the instability of legislation, the limitation of control powers, and the inconsistency of national mechanisms with the international obligations of the state are identified. The need for a comprehensive approach to the implementation of international standards, combining legislative, institutional, and organizational measures, is substantiated. It is concluded that increasing the institutional capacity of labor supervision and control bodies is an important prerequisite for the effective protection of labor rights of employees and the harmonization of Ukrainian legislation with European social and legal standards.